2003
DOI: 10.1111/j.1939-1676.2003.tb02501.x
|View full text |Cite
|
Sign up to set email alerts
|

Biologic Behavior and Prognostic Factors for Mast Cell Tumors of the Canine Muzzle: 24 Cases (1990–2001)

Abstract: The medical records of 24 dogs with histologically confirmed mast cell tumors (MCT) of the muzzle were retrospectively evaluated to determine their biologic behavior and prognostic factors. Information on signalment, tumor grade and stage, treatment methods, and pattern of and time to failure and death was obtained from the medical record. Twenty-three dogs were treated with combinations of radiotherapy, surgery, and chemotherapy; 1 dog received no treatment. There were 2 Grade I, 15 Grade II, and 7 Grade III … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
2
13

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(106 citation statements)
references
References 23 publications
2
89
2
13
Order By: Relevance
“…Grade has been shown by many investigators to correlate with outcome in canine MCT [29], and some investigators have likewise suggested that mucocutaneous location may be associated with more aggressive biologic behavior [29,30]. One report described aggressive behavior for MCT of the canine muzzle [11], however it did not specify how many arose from mucous membrane versus haired skin of the muzzle. To our knowledge, this is the first study that has demonstrated a statistical association between mucous membrane origin and outcome in canine MCT.…”
Section: Discussionmentioning
confidence: 99%
“…Grade has been shown by many investigators to correlate with outcome in canine MCT [29], and some investigators have likewise suggested that mucocutaneous location may be associated with more aggressive biologic behavior [29,30]. One report described aggressive behavior for MCT of the canine muzzle [11], however it did not specify how many arose from mucous membrane versus haired skin of the muzzle. To our knowledge, this is the first study that has demonstrated a statistical association between mucous membrane origin and outcome in canine MCT.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, reporting should be thorough and inclusive. In veterinary medicine, a variety of assays and techniques have been used in attempts to identify prognostic markers for neoplastic diseases, including clinical parameters, 1,18,24 histologic features, 27,42,46 immunohistochemistry, 33,56 quantitative PCR, 16 evaluations for genomic mutations, 57 and specific serum protein levels or enzyme activity analyses. 17,25 The variety of assays used to identify prognostic markers will likely increase as new technologies are developed.…”
Section: Methods Of Prognostic Marker Evaluationmentioning
confidence: 99%
“…MCTs of the muzzle (35) and perineal or preputial (23) areas appear to have higher regional metastatic potential than those in other sites. Mastocytaemia, reported to occur in cats (3) and dogs (4,61,83,111) with MCTs as an indicator of haematogenous spread, should be regarded with caution.…”
Section: Canine Mast Cell Tumours Epidemiology and Aetiologymentioning
confidence: 99%
“…Several investigators have attempted to apply histologic grading systems based on the degree of differentiation (1,11,35,36,42,47,71,86) of the tumours. The purpose of histologic grading of MCTs is not only to assist the pathologist in giving a more accurate prognosis in each individual, but it will provide also a base-line against which the effects of clinical trials involving additional therapies can be measured (11).…”
Section: A Histologic Gradementioning
confidence: 99%